2014
DOI: 10.1021/bi500773c
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Highly Ordered Multimers in G-Quadruplexes

Abstract: G-Rich DNA and RNA have a higher propensity to form G-quadruplex structures, but the presence of G-runs alone is not sufficient to prove that such sequences can form stable G-quadruplexes. While G-rich sequences are essential for G-quadruplex formation, not all G-rich sequences have the propensity to form G-quadruplex structures. In addition, monovalent metal ions, dehydrating agents, and loop sequences connecting the G-runs also play important roles in the topology of G-quadruplex folding. To date, no quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 57 publications
4
48
0
1
Order By: Relevance
“…2). 20,21 The similar spectrum was recorded for the complex of the probe and TDNA (Fig. 2 (curve 1), the spectrum of the probe (in the presence of K + and Na + cations) has a positive signal at around 264 nm and a negative signal at 242 nm, which are characteristic of parallel G-quadruplexes.…”
Section: Resultssupporting
confidence: 55%
“…2). 20,21 The similar spectrum was recorded for the complex of the probe and TDNA (Fig. 2 (curve 1), the spectrum of the probe (in the presence of K + and Na + cations) has a positive signal at around 264 nm and a negative signal at 242 nm, which are characteristic of parallel G-quadruplexes.…”
Section: Resultssupporting
confidence: 55%
“…3. 21,32 Moreover, we showed that CD spectra of PMDNAzyme(T 10 ) in the presence and in the absence of K + cations were practically identical, whereas CD spectra of NH 2 -T 10 -EAD2 changed (Fig. 21 The similar spectrum was measured for the aptamer NH 2 -T 10 -EAD2 itself.…”
Section: Study Of the Synthesized Covalent Pmdnazymes Topologysupporting
confidence: 57%
“…Depending on the topological arrangement of the G‐rich strands participating in their formation, G‐wires can be classified into two categories: i) interlocked G‐wires , characterized by the cooperative assembly of interlocked slipped strands (Figure B) and ii) stacked G‐wires , characterized by the multimerization of G‐quadruplex building blocks held together by end‐to‐end π–π stacking (Figure C). Besides the well‐known interlocked G‐wires and G‐wires containing both topological motifs, only a few examples of exclusively stacked G‐wires have been reported so far …”
Section: Introductionmentioning
confidence: 99%